Inequality and Mobility of Wealth in Sweden 1983/84 - 1992/93 - Lars Bager-Sjögren; N. Anders Klevmarken (Uppsala University, Department of Economics, 1997)
Using longitudinal data which include real estate wealth, financial assets as well as consumer durables, changes in the distribution of wealth in Sweden are related to major changes in asset prices and in incentives to hold various assets in the 1980s and the beginning of the 1990s. Our analysis of the mobility of wealth indicates that mobility is higher in Sweden than in the United States, while the analysis of who is gaining and who is loosing shows results similar to those of previous studies.
urn:nbn:se:uu:diva-2381
Keywords: 330